Optimization of alkaline protease production by Bacillus cereus FT 1isolated from soil - B. Asha & , M. Palaniswamy (Journal of Applied Pharmaceutical Science, 2018)
Alkaline proteases have high commercial value and find multiple applications in various industrial sectors. The present study intended to isolate a suitable bacterium for alkaline protease production. Protease producing bacteria were isolated from organic waste containing soil, screened for protease production on skim milk agar plates and confirmed the protease production through protease assay. The bacterial isolate showing highest alkaline protease production was selected and identified by microscopic, macroscopic, biochemical and 16 S RNA phylogenetic analyses as Bacillus cereus FT 1. Maximum enzyme production by the isolate was obtained at 35°C; pH, 9.5; 2% lactose as a carbon source and 3.5% casein as a nitrogen source after 48 h of incubation. Among the various surfactants tested, tween 20, tween 80 and poly ethylene glycol were found to be increasing the protease production by the isolate. Mn2+, among the metal ions tested tremendously increased the protease production. The best organic solvent for protease production was found to be petrol. With all the optimised cultural conditions, maximum enzyme activity was found to be 187 U/mL and the enzyme was a promising one for detergent industry as an additive enzyme.
Keywords: Alkaline protease, Fermentation,Protease assay, Bacilluscereus, Protease production,Screening, Optimization.